Comparative Study Of A Low Rise Building Design Using Ec2 And Bs8110 - Duong Vannak, Duong Vannak (Universiti Teknologi Petronas, 2010)
This report is intended to raise awareness amongst the Structural Engineering Profession of the forthcoming Eurocode for the Design of Concrete Structures EC2 which will in a few years replace the existing British code BS8110